“Efecto de (magnet B) fosfonato de calcio boro en el cultivo de lechuga (lactuca sativa) variedad greak lakes 659, en la provincia de Lamas” - López Carhuatanta, Wilson Fidel (2014)
The present investigation entitled "Effect of (Magnet B) of calcium phosphonate - boron in growing lettuce (Lactuca sativa.L), Great Lakes 659 range, in the Province of Lamas" The objective was to assess the effects on crop yields of lettuce (Lactuca sativa L.) with application of 4 doses of calcium phosphonate - boron in the Province of Lamas. The present research was conducted from August to October 2012, the block design was completely randomized, with 5 treatments and 4 blocks . The results we obtained indicate that all the variables studied had a direct relationship with performance. The T3 (0.75 1 I ha-1) treatment reached the highest average with Kg.ha 33,368,8-1 in which performance and statistically surpassed others, followed by other treatments T2 (0.5 Kg I ha) T4 (1.0 Kg I ha) T1 (0.25 Kg I ha) and TO .All treatments yielded indices B I C above zero being the T3 (0.75 Kg.ha Magnet B-1 treatment had the best B I C with 1.46 followed by T2 (0.5 Kg I ha-1), T4 Magnet B (1.0 Kg I ha-1) Magnet B, the T1 (0.25 kg ha-1) of Magnet B and TO (control) with values of 1.41, 1.38, 1.06 and 0.91 respectively. These results demonstrate that increasing the dose of Magnet B, repercuto directly into increased performance Kg.ha-1 and therefore in increasing the profitability of growing lettuce. Keywords: Lettuce, variety, Great, Lakes Magnet B, phosphonate, calcium, boron